Isolation, Identification and Drug Resistance Research of Klebsiella pneumoniae in Drinking Water from a Chicken Farm - Dejia FU; Huahua KANG; Xianjun ZENG; Zhihong FAN; Jie CHEN; Weiqian HUANG; Shunjin JIANG; Xinyu PENG (Guangdong nongye kexue, 2024)
【Objective】It aims to investigate resistance phenotypes and resistance genes of Klebsiella pneumoniae in drinking water of chicken farm, and analyze the correlation between them, to provide references for effective prevention of the disease.【Method】Strains of K. pneumoniae were isolated and identified from the drinking water system of a chicken farm.The resistances of the isolated strains to 25 antibiotics were detected by the drug-sensitive disk diffusion method. The presence of common drug-resistance genes in all these strains was detected by PCR. The whole genomes of four strains of K. pneumoniae were sequenced to analyze and predict the carrying of drug resistance genes by the Comprehensive Antibiotic Research Database (CARD).【Result】Nine strains of K. pneumoniae were isolated from the drinking water system of the chicken farm.The results of drug sensitivity testing revealed that these strains were multiple drug resistant, and only susceptive to colistin sulfate. Thirteen common drug resistance genes carried by all nine strains were confirmed by PCR, and consistency between drug resistance phenotypes and genes was observed in 12 resistant genes including β-lactamase resistance genes CMY-1, BlaSHV and BlaCTX-M; carbapenem resistance gene KPC; quinolone resistance genes QnrB, QnrS and QnrA; aminoglycoside resistance gene Aph(3')-Ia; sulfa resistance gene Sul2 and etc; while inconsistency between the presence of Mcr-1 and its corresponding phenotype was observed. A total of 59 resistance genes, involving 31 classes of antibiotics, were carried by four strains of K. pneumoniae through whole genome scanning analysis. Among these, the number of genes resistant to tetracycline antibiotics was maximum, followed by genes resistant to macrolide and fluoroquinolone antibiotics. Additionally, a total of 23 drug-resistant genes were predicted when the coverage and homology were both set at a rate of higher than 98%, including FosA6, CRP, KpnF, KpnFG, KpnE, OqxA, OqsB, SHV-11, Tet(D), CTX-M-27, QnrB65, DHA-1, Aph(4')-Ia, MsrE, QnrB2, Aph(3')-Ia, Sul1, CmlA6, FloR, AadA12, Ant(3'')-IIa, ArmA and Sul2.【Conclusion】Strains of K. pneumoniae isolated from the drinking water of the chicken farm show serious drug resistance and carried multiple drug resistance genes, among which Mcr-1 gene is detected on the isolated strains. However, the isolated strains are sensitive to polymyxin, and the D-type carbapenemase OXA-48 gene was not detected in the isolated strains.